Determination of the Explosion Characteristics of Wheat Flour - Kuracina Richard (Research Papers. Faculty of Materials Science and Technology. Slovak University of Technology in Trnava, 2017)
The article deals with the measurement of explosion characteristics of wheat flour. The measurements were carried out according to STN EN 14034-1+A1:2011 Determination of explosion characteristics of dust clouds. Part 1: Determination of the maximum explosion pressure pmax of dust clouds, the maximum rate of explosion pressure rise according to STN EN 14034-2+A1:2012 Determination of explosion characteristics of dust clouds - Part 2: Determination of the maximum rate of explosion pressure rise (dp/dt)max of dust clouds and LEL according to STN EN 14034-3+A1:2011 Determination of explosion characteristics of dust clouds: Determination of the lower explosion limit LEL of dust clouds. The testing of explosions of wheat flour dust clouds showed that the maximum value of the pressure was reached at the concentrations of 600 g/m3 and its value is 8.32 bar/s. The fastest increase of pressure was observed at the concentration of 750 g/m3 and its value was 54.2 bar/s.